VALIDATION OF THE MACNEW QUESTIONNAIRE FOR THE ASSESSMENT OF HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH ISHEMIC HEART DISEASE - N. V. Pogosova; A. A. Kursakov; I. H. Boycharov; S. Höfer; N. Oldridge (Рациональная фармакотерапия в кардиологии)
Background. Recently, a greater emphasis is being placed on health-related quality of life (HRQL) in both global and Russian practice. In many countries HRQL in patients with ischemic heart disease (IHD) is assessed by a disease-specific questionnaire – The MacNew Heart Disease HRQL questionnaire (MacNew) – that has been validated in many countries, but not yet in Russia.Aim. To validate Russian MacNew questionnaire in patients with different clinical types of ICD.Material and methods. Direct and reverse translation of the MacNew questionnaire was performed in accordance with the protocol of international HeartQol study. The patients (n=322) with angina, myocardial infarction, and heart failure were enrolled into the study and completed the Short-Form 36 (SF-36), the Hospital Anxiety and Depression Scale (HADS) and the Mac-New at the baseline; approximately 20% of the patients were reexamined 2 weeks later. The conceptual framework, reliability and validity of the Russian version of MacNew HRQL questionnaire were assessed.Results. The Russian version of MacNew questionnaire demonstrated sufficient internal consistency with Cronbach’s α exceeding 0.80. High test-retest reliability of the questionnaire was established in the total sample of ICD patients (0.949; p<0.01). Factor analysis in general substantiated the conceptual model of the Russian version of MacNew and its satisfactory content validity. Convergent validity was confirmed by strong correlations between the subscales of Russian MacNew questionnaire and conceptually similar subscales of the SF-36 survey (in the total sample and in separated clinical groups. Discriminant validity of the Russian version of MacNew was also confirmed differentiating patients with different SF-36 health transition and patients with and without anxiety and depression (HADS questionnaire).Conclusions. The Russian version of MacNew HRQL questionnaire has demonstrated adequate reliability and validity as compared with the original method. It can be recommended for the assessment of life quality in Russian-speaking patients with various types of ICD in daily clinical practice and research work.